Herrens bøn „Fadervor“ - Ludvigsen, Valdemar Leth (Grundtvig-Studier, 1977)
The Lord’s Prayer by Valdemar Leth Ludvigsen My starting-point was an analysis of Grundtvig’s view of the Lord’s presence at baptism. This examination showed that the Lord’s prayer, which is also the baptismal prayer, acquired increasing significance for Grundtvig around 1840. It was then my aim to reach an understanding of the Lord’s prayer as a reason for this growing influence. With the aid of Sangværket (the Collection of Songs) and on the basis of published as well as unpublished sermons it appeared that the Lord’s prayer in Grundtvig has become a gospel word, to be professed. The basic idea is that praying is not only a question of saying the Lord’s prayer. For through His presence in the Spirit the Lord united Himself with those at prayer and prays together with them. This fact has its roots in both the Lord’s incarnation — Christmas - and in the worshippers’ baptism, when God comes to the aid of the man in distress to make him His child again. Praying together with the Lord the worshippers’ prayer fuses together with the Lord’s own voice, so that the Heavenly Father can hear His own Son’s voice in the prayer. Whatever the Son asks the Heavenly Father is always granted. Therefore the prayers of those whose voice is united with the Lord’s own are also granted through faith in Him. The ‘amen’ of the prayer must be heard by the worshippers at the Heavenly Father’s, the Creator’s own confirmation of the fulfilment of the prayer. Everything that is covered by the words of the Lord’s prayer is thereby granted to the worshippers. In this way the Lord’s prayer becomes both a putting forward of the words of the prayer and an audible gospel. Since the prayer as an audible gospel rests on the Lord’s own presence in the Spirit, the worshippers experience an anticipatory fulfilment of the requests in the prayer. This is expressed as a renewal of faith, which nourishes a living hope. This guarantees the final fulfilment of the Christian hope. Just as this is expressed in the thanksgiving song of praise by the enlightened congregation, so is the present hope made manifest in an anticipatory song of praise. The worshippers can hum the prayer. With this view of the Lord’s prayer we have reached an understanding of what lies behind the growing significance of the prayer for Grundtvig.